The sugar ring conformation of 4'-ethynyl-2-fluoro-2'-deoxyadenosine and its recognition by the polymerase active site of HIV reverse transcriptase - Kirby, K. A.; Singh, K.; Michailidis, E.; Marchand, B.; Kodama, E. N.; Ashida, N.; Mitsuya, H.; Parniak, M. A.; Sarafianos, S. G. (Cellular and Molecular Biology, 2011)
4'-Ethynyl-2-fluoro-2'-deoxyadenosine (EFdA) is the most potent inhibitor of HIV reverse transcriptase (RT). We have recently named EFdA a Translocation Defective RT Inhibitor (TDRTI) because after its incorporation in the nucleic acid it blocks DNA polymerization, primarily by preventing translocation of RT on the template/primer that has EFdA at the 3'-primer end (T/PEFdA). The sugar ring conformation of EFdA may also influence RT inhibition by a) affecting the binding of EFdA triphosphate (EFdATP) at the RT active site and/or b) by preventing proper positioning of the 3'-OH of EFdA in T/PEFdA that is required for efficient DNA synthesis. Specifically, the North (C2'-exo/C3'-endo), but not the South (C2'-endo/C3'-exo) nucleotide sugar ring conformation is required for efficient binding at the primer-binding and polymerase active sites of RT. In this study we use nuclear magnetic resonance (NMR) spectroscopy experiments to determine the sugar ring conformation of EFdA. We find that unlike adenosine nucleosides unsubstituted at the 4'-position, the sugar ring of EFdA is primarily in the North conformation. This difference in sugar ring puckering likely contributes to the more efficient incorporation of EFdATP by RT than dATP. In addition, it suggests that the 3'-OH of EFdA in T/PEFdA is not likely to prevent incorporation of additional nucleotides and thus it does not contribute to the mechanism of RT inhibition. This study provides the first insights into how structural attributes of EFdA affect its antiviral potency through interactions with its RT target.